Water treatment using Moringa oleifera seed extract: An integrative review (Research, Society and Development, 2022)
The use of coagulants of natural origin in water treatment is an ecological alternative that has been viable in the replacement of chemical coagulants. One of the examples of a natural coagulant is the seed of the Moringa oleifera plant, whose application in research, testing and analysis has been gaining ground. The seed extract, as it contains a cationic protein, acts as a clarifying agent in water treatment. The present work aimed to highlight the use of Moringa oleifera as a natural coagulant and flocculant in water treatment, through an integrative review study. A bibliographic survey was carried out in the SciElo and Google academic databases and 10 (ten) articles were selected corresponding to the objective of the study. Based on the studies analyzed, the literature confirms that Moringa oleifera seeds are effective in water treatment, focusing on the reduction of physical-chemical (turbidity and color) and microbiological parameters, and without significant change in pH. Therefore, the application of natural coagulant in water treatment is an economically viable and environmentally sustainable alternative.